STEM Students' Engagement in Horizontal Transfer from Calculus to Physics and their Difficulties - Q. Quimson, Jerrie-Marie (Universitas Terbuka, 2021)
Majority of science students are facing different problems in applying their calculus knowledge to physics courses. Researchers started to develop an integrated approach to address this problem however, many schools are still teaching calculus and physics as two separate subjects. Moreover, there has been no significant research on senior high school students' transfer of learning and difficulties in calculus-based physics subjects. It is crucial because this is when the students first experience applying calculus in a physics context. Hence, the study investigated the engagement of senior high school STEM students to horizontal transfer from Basic Calculus to General Physics subjects and the difficulties they experience in solving calculus-based-physics problems. A correlational study research design was employed to explore the relationship between the students’ physics and calculus performance using a physics worksheet. Both qualitative and quantitative methods were also employed to determine the difficulties of the students in calculus-based-physics problems. The Pearson correlation revealed that there is a significant positive correlation between the students’ physics and calculus performance. Although this could not serve as strong evidence of transfer, this strong correlation implies that senior high school STEM students were able to construct the similarities between the calculus-based physics problems and their calculus schema. As revealed in the questionnaire and the students’ responses in the worksheet and interview, students have difficulty in solving calculus-based physics problems in terms of identifying the variable that needs to be integrated, setting-up the limits of integration, evaluating the limits of integral, and identifying the appropriate rules of integration and applying it in solving the physics problem. These difficulties are rooted in the fact that students have little experience applying calculus in word problems, especially in the physics context.